(untitled) - Blum, Richard (San Francisco, 2003)
Network Programming Basics (The C# Language; IP Programming Basics; C# Network Programming Classes; DNS and C#); Network Layer Programing (Connection-Oriented Sockets; Connectionless Sockets; Using The C# Sockets Helper Classes; Asynchronous Sockets; Using Threads; IP Multicasting); Application Layer Programming Examples (ICMP; SNMP; SMTP; HTTP; Active Directory; Remoting; Security)
Keywords: Computer program language -- C#; Internet programming; Công nghệ thông tin -- Ngôn ngữ lập trình -- C#; Lập trình mạng